Major heme proteins hemoglobin and myoglobin with respect to their roles in oxidative stress – a brief review - Sil, Rajarshi; Chakraborti, Abhay Sankar (Frontiers in Chemistry, 2025)
Oxidative stress is considered as the root-cause of different pathological conditions. Transition metals, because of their redox-active states, are capable of free radical generation contributing oxidative stress. Hemoglobin and myoglobin are two major heme proteins, involved in oxygen transport and oxygen storage, respectively. Heme prosthetic group of heme proteins is a good reservoir of iron, the most abundant transition metal in human body. Although iron is tightly bound in the heme pocket of these proteins, it is liberated under specific circumstances yielding free ferrous iron. This active iron can react with H2O2, a secondary metabolite, forming hydroxyl radical via Fenton reaction. Hydroxyl radical is the most harmful free radical among all the reactive oxygen species. It causes oxidative stress by damaging lipid membranes, proteins and nucleic acids, activating inflammatory pathways and altering membrane channels, resulting disease conditions. In this review, we have discussed how heme-irons of hemoglobin and myoglobin can promote oxidative stress under different pathophysiological conditions including metabolic syndrome, diabetes, cardiovascular, neurodegenerative and renal diseases. Understanding the association of heme proteins to oxidative stress may be important for knowing the complications as well as therapeutic management of different pathological conditions.